2016
DOI: 10.1038/srep34030
|View full text |Cite
|
Sign up to set email alerts
|

Large area Germanium Tin nanometer optical film coatings on highly flexible aluminum substrates

Abstract: Germanium Tin (GeSn) films have drawn great interest for their visible and near-infrared optoelectronics properties. Here, we demonstrate large area Germanium Tin nanometer thin films grown on highly flexible aluminum foil substrates using low-temperature molecular beam epitaxy (MBE). Ultra-thin (10–180 nm) GeSn film-coated aluminum foils display a wide color spectra with an absorption wavelength ranging from 400–1800 nm due to its strong optical interference effect. The light absorption ratio for nanometer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…1. The present discussion in the literature regarding the band gap evolution of GeSn alloys is based on the assumption that with increasing Sn composition there is a sharp transition from GeSn being an indirect band gap material to a direct one 18,19,25–27 . However, there is a large degree of uncertainty for the Sn concentration at which this transition occurs, with typical values ranging from ~6–11% Sn 2831 .…”
Section: Introductionmentioning
confidence: 99%
“…1. The present discussion in the literature regarding the band gap evolution of GeSn alloys is based on the assumption that with increasing Sn composition there is a sharp transition from GeSn being an indirect band gap material to a direct one 18,19,25–27 . However, there is a large degree of uncertainty for the Sn concentration at which this transition occurs, with typical values ranging from ~6–11% Sn 2831 .…”
Section: Introductionmentioning
confidence: 99%
“…Nonequilibrium surface growth by means of molecular beam epitaxy (MBE) is one of the most widely used techniques to fabricate thin film devices for various technological applications [1][2][3][4]. Since the growth conditions can be precisely controlled, MBE also serves as an exemplary experimental setup to study fundamental aspects of nonequilibrium statistical mechanics [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…% Sn). Formation of a metastable Ge–Sn alloy through electrodeposition is highly interesting, as Sn and Ge are immiscible at room temperature under equilibrium and alloys are prepared through high input energy techniques such as sputtering or other physical evaporation techniques. , Early studies revealed that electrodeposition of Ge could be induced in the presence of a second metal ion in the electrolyte such as Ni, Cu, or Ga because in these cases the corresponding alloy is thermodynamically favored and provides a reaction pathway. , For instance, Zhao et al have shown that the formation of a Cu 3 Ge thin film on a gold substrate by electrodeposition is mainly related to the formation of a more thermodynamically favored Ge–Cu bond. However, according to the Ge–Sn phase diagram, the formation of a Ge–Sn alloy is thermodynamically prohibited.…”
Section: Resultsmentioning
confidence: 99%